Management accounting - Bhattacharyya, Debarshi (Pearson, 2011)
Management Accounting is a comprehensive textbook with a focus on the essentials, designed to help students understand the basic concepts and practice underlying management accounting in a systematic manner. A balanced approach between theoretical and numerical aspects of the subject has been adopted to ensure ease and clarity in learning. The lucid writing, contents and organization of the chapters make the book eminently suitable for the undergraduate students of various Indian Universities.